Cutaneous Aβ-Non-nociceptive, but Not C-Nociceptive, Dorsal Root Ganglion Neurons Exhibit Spontaneous Activity in the Streptozotocin Rat Model of Painful Diabetic Neuropathy in vivo - Djouhri, Laiche; Zeidan, Asad; Abd El-Aleem, Seham A.; Smith, Trevor (Frontiers in Neuroscience, 2020)
Diabetic peripheral neuropathic pain (DPNP) is the most devastating complication of diabetes mellitus. Unfortunately, successful therapy for DPNP remains a challenge because its pathogenesis is still elusive. However, DPNP is believed to be due partly to abnormal hyperexcitability of dorsal root ganglion (DRG) neurons, but the relative contributions of specific functional subtypes remain largely unknown. Here, using the strepotozotocin (STZ) rat model of DPNP induced by a STZ injection (60 mg/kg, i.p), and intracellular recordings of action potentials (APs) from DRG neurons in anesthetized rats, we examined electrophysiological changes in C-and Aβ-nociceptive and Aβ-low threshold mechanoreceptive (LTM) neurons that may contribute to DPNP. Compared with control, we found in STZ-rats with established pain hypersensitivity (5 weeks post-STZ) several significant changes including: (a) A 23% increase in the incidence of spontaneous activity (SA) in Aβ-LTMs (but not C-mechanosensitive nociceptors) that may cause dysesthesias/paresthesia suffered by DPNP patients, (b) membrane hyperpolarization and a ∼85% reduction in SA rate in Aβ-LTMs by Kv7 channel activation with retigabine (6 mg/kg, i.v.) suggesting that Kv7/M channels may be involved in mechanisms of SA generation in Aβ-LTMs, (c) decreases in AP duration and in duration and amplitude of afterhyperpolarization (AHP) in C-and/or Aβ-nociceptors. These faster AP and AHP kinetics may lead to repetitive firing and an increase in afferent input to the CNS and thereby contribute to DPNP development, and (d) a decrease in the electrical thresholds of Aβ-nociceptors that may contribute to their sensitization, and thus to the resulting hypersensitivity associated with DPNP.